2020
DOI: 10.1038/s41467-020-16691-x
|View full text |Cite
|
Sign up to set email alerts
|

NAP1-RELATED PROTEIN1 and 2 negatively regulate H2A.Z abundance in chromatin in Arabidopsis

Abstract: In eukaryotes, DNA wraps around histones to form nucleosomes, which are compacted into chromatin. DNA-templated processes, including transcription, require chromatin disassembly and reassembly mediated by histone chaperones. Additionally, distinct histone variants can replace core histones to regulate chromatin structure and function. Although replacement of H2A with the evolutionarily conserved H2A.Z via the SWR1 histone chaperone complex has been extensively studied, in plants little is known about how a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…This splicing factor, which belongs to a zinc finger CCCH domain-containing protein that is proposed to be important in the salt tolerance of plants, is upregulated six-fold in quinoa GCs [ 33 ]. NAP1-related protein X2, which belongs to a family of chaperones and is involved in DNA repair, is also critical under stress conditions [ 34 ]. This protein was also upregulated under salt stress (two-fold).…”
Section: Resultsmentioning
confidence: 99%
“…This splicing factor, which belongs to a zinc finger CCCH domain-containing protein that is proposed to be important in the salt tolerance of plants, is upregulated six-fold in quinoa GCs [ 33 ]. NAP1-related protein X2, which belongs to a family of chaperones and is involved in DNA repair, is also critical under stress conditions [ 34 ]. This protein was also upregulated under salt stress (two-fold).…”
Section: Resultsmentioning
confidence: 99%
“…Distinct from the sole OsChz1, NAP1 is represented by a family of 5–6 members in rice or Arabidopsis 25 . Interestingly, a recent study showed that the Arabidopsis NRP1 and NRP2 negatively regulate H2A.Z abundance in chromatin and their loss causes over-accumulation of H2A.Z genome-wide, especially at heterochromatin regions normally depleted for H2A.Z in wild-type plants 34 . In parallel to specific functions, it is worth to note that redundant functions also exist between Chz1 and NAP1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the prediction by the anti-correlation rule, the decreased level of H2A.Z was observed without any detectable increase of DNA methylation in the rice oschz1 mutant (this study). Also, loss of H2A.Z in Arabidopsis has only a minor effect on DNA methylation 20 , and the nrp1-1nrp2-2 mutant displays H2A.Z accumulation but largely unaltered DNA methylation or even slight increases of CG/CHG methylation at some TEs 34 . Together, these studies support the proposition that the global anti-correlation between DNA methylation and H2A.Z is primarily caused by the exclusion of H2A.Z from methylated DNA 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NRP proteins localized predominantly in the nucleus ( Gonzalez-Arzola et al, 2017 ) genetically interact with the SWR1 core components and link with H2A.Z. It is proposed that, in Arabidopsis , NRP proteins counteract the activity of the SWR1 complex and associate with the dynamic regulation of H2A.Z ( Wang et al, 2020 ).…”
Section: Chromatin Modifications In Plant Stress Tolerancementioning
confidence: 99%